Laminated Ag and Ag/CNT nanocomposite films as sensing element for efficient thin film temperature sensors. (February 2021) - Sarma, Shrutidhara; Singh, Surinder; Garg, A.
Highlights: Ag-CNT nanocomposite sensor showed a better temperature coefficient of resistance. Ag-CNT nanocomposite sensors have higher sensitivity compared to conventional counterparts. Ag-CNT nanocomposite TFS has a higher TCR compared to the only Ag TFS by 46.4%. Abstract: Thin film sensor (TFS) is one of the most promising candidates for instantaneous temperature measurements owing to their extremely small response time ( milliseconds) aided with fair accuracy. Since they are capable of making quick and precise temperature measurements, they can be also used as heat flux gauges to measure surface heat fluxes in dynamic environments like high speed aerospace applications, gas turbine blades etc. Usual TFS are made by depositing a thin metallic film over insulating substrate. In this work we developed an Ag-Carbon nanotube (CNT) nanocomposite film as the sensing element of a TFS and compare it with pure Ag TFS, both having Macor as substrate. Static calibration established a better temperature coefficient of resistance (TCR) value i.e. better sensitivity, for the nanocomposite TFS. X-ray diffraction (XRD) and Energy Dispersive X-ray (EDX) studies are done to probe behind the increase in sensitivity of the nanocomposite TFS compared to its conventional metallic counterpart.